Experimental Study of Lime-Gravel columns Technique for the Stabilization of Expansive Soils - اسطه, رامي; نظام, نورا (Latakia University Journal -Engineering Sciences Series, 2021)
Previous theoretical studies provide clear evidence of the effectiveness of soil improvement using lime, which necessitates increased interest in the study of new lime-based techniques in the process. This research is based on the experimental approach, where a set of tests were conducted to study the effect of treatment time and distance from the improvement column by conducting a set of experiments such as Atterberg limits, free swell, direct shear and consolidation. The model designed for the study is a metallic cylindrical mold filled with expansive clay from Demsarkhu area and a central cylindrical hole filled with gravel and lime mixed with 50% of the weight of the gravel. The tested samples are extracted (1D-2D-3D-4D-5D) from the column diameter –where D is the column diameter- and also at Treatment periods of(7-28-57-112) days after the Implementation of the improvement column, the results showed a clear decrease in the values ​​of plasticity index and the free swell index as well as an increase in shear resistance and soil elasticity coefficient by increasing the treatment period and decreasing the distance from the column.